Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

What is the equation of the line that passes through (-1, -4) and (-2, -1) y = 2x - 1 y = 2x - 1 y = -2x - 4 y = -2x - 4 y = 3x - 7 y = 3x - 7 y = -3x - 7

Sagot :

Answer:

(-1, -4) and (-2, -1) y = 2x - 1 y = 2x - 1 y = -2x - 4 y = -2x - 4 y = 3x - 7 y = 3x - 7 y = -3x - 7

Explanation: